2016
DOI: 10.1097/mjt.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Feasibility, and Efficacy of Capecitabine Maintenance in Patients With Advanced Gastric Cancer: A Retrospective Study

Abstract: Gastric cancer is still one of the cancers with highest mortality. Most patients present with advanced-stage disease. Palliative chemotherapy is usually the only treatment option for patients with advanced gastric cancer (AGC). Maintenance chemotherapy is an evolving concept in medical oncology. Maintenance chemotherapy can be administered with the same drug(s) in the initial regimen or with an alternative agent. In this article, we report our experience with capecitabine as a maintenance agent for patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…In patients with colorectal cancer, this theory is supported by data from the CAIRO3 study (Treatment with Capecitabine and Bevacizumab Versus Observation), which demonstrated that maintenance significantly delayed PFS and was associated with a trend toward longer OS compared with observation after induction chemoimmunotherapy . In this study, maintenance treatment was found to be feasible and did not lead to excessive toxicity, a finding that is in keeping with 2 previous studies . Feasibility of the B‐DOC regimen was further demonstrated by adequate RDI for the administered drugs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In patients with colorectal cancer, this theory is supported by data from the CAIRO3 study (Treatment with Capecitabine and Bevacizumab Versus Observation), which demonstrated that maintenance significantly delayed PFS and was associated with a trend toward longer OS compared with observation after induction chemoimmunotherapy . In this study, maintenance treatment was found to be feasible and did not lead to excessive toxicity, a finding that is in keeping with 2 previous studies . Feasibility of the B‐DOC regimen was further demonstrated by adequate RDI for the administered drugs.…”
Section: Discussionsupporting
confidence: 83%
“…10 In this study, maintenance treatment was found to be feasible and did not lead to excessive toxicity, a finding that is in keeping with 2 previous studies. 11,20 Feasibility of the B-DOC regimen was further demonstrated by adequate RDI for the administered drugs. The achieved RDI for capecitabine during the first 6 cycles was somewhat lower than expected (75%-80%), but is in keeping with a recent study that demonstrated that the RDI was 74% in patients treated with a similar DOC regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Small studies have suggested that fluoropyrimidine-based maintenance therapy is feasible in patients with GC/GEJC, although data are limited [34][35][36]. Trastuzumab and ramucirumab are administered until disease progression [7]; thus, their clinical efficacy benefits in patients with GC/GEJC may be due in part to maintenance treatment [19].…”
Section: Rationale For Maintenance Therapy In Gc/gejcmentioning
confidence: 99%
“…Furthermore, reintroduction of the 1L chemotherapy regimen following disease progression on (switch) maintenance treatment is also possible [18]. Although maintenance treatment for advanced GC/GEJC has not been studied extensively, observational and retrospective studies reported to date have shown that maintenance treatment with fluoropyrimidines is feasible and may improve PFS compared with observation [19][20][21]. Moreover, trastuzumab or ramucirumab are administered continuously until disease progression in patients with GC/GEJC [5], suggesting that evaluation of long-term treatment with other agents is warranted.…”
mentioning
confidence: 99%